2020
DOI: 10.1111/jfb.14396
|View full text |Cite
|
Sign up to set email alerts
|

Dietary specificity and overlap in endorheic river fishes: How do native and nonnative species compare?

Abstract: The introduction of nonnative species is one of the most critical problems facing freshwater systems today. The rivers of the Great Basin (USA) have been particularly imperilled by nonnative species introductions and represent a valuable location to study the dietary trends of native and nonnative fishes in isolated, endorheic systems. We collected fish from 23 sites, spanning three Great Basin watersheds (Carson, Humboldt and Bear Rivers) and two elevation categories (upland and lowland). Only a single specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
(99 reference statements)
0
6
0
Order By: Relevance
“…Fishes that did assimilate EAAs of terrestrial origin were mostly minnows or large salmonids, which may have been most likely to consume terrestrial detritus or terrestrial insects, respectively. However, terrestrial invertebrates known to provide important resource subsidies to stream consumers (Nakano & Murakami, 2001) were not observed in significant amounts in fish stomachs at the time of sampling (Minder et al, 2020, 2021). Because we did not analyse the δ 13 C EAA profiles of invertebrates, we cannot be certain about the value of direct terrestrial assimilation for organisms that feed directly on decomposing terrestrial organic matter (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Fishes that did assimilate EAAs of terrestrial origin were mostly minnows or large salmonids, which may have been most likely to consume terrestrial detritus or terrestrial insects, respectively. However, terrestrial invertebrates known to provide important resource subsidies to stream consumers (Nakano & Murakami, 2001) were not observed in significant amounts in fish stomachs at the time of sampling (Minder et al, 2020, 2021). Because we did not analyse the δ 13 C EAA profiles of invertebrates, we cannot be certain about the value of direct terrestrial assimilation for organisms that feed directly on decomposing terrestrial organic matter (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…2A) and the literature on ecological impacts. Indeed, field data and experiments have repeatedly shown that the trophic niches of invasive and native fish species overlap (Schleuter, 2007;Sampson et al, 2009;Minder et al, 2020). In addition, invasive fish also compete with organisms found outside their freshwater habitats, such as riparian spiders and birds Jackson et al, 2016).…”
Section: Competitionmentioning
confidence: 99%
“…Gut content analysis was based on methods used in Minder et al. (2020). Guts (esophagus to pyloric valve) were evacuated of all contents and weighed, and contents were examined under a dissecting scope.…”
Section: Methodsmentioning
confidence: 99%